Kit used for diagnosing human enterovirus infection - ZHONG SHAN; MA DONGLI (2017)
The invention provides a kit used for diagnosing human enterovirus infection. The detection kit comprises one or more solid carriers, and polypeptide independently connected with the solid carriers and shown as SEQ ID NO: 1-10. When whether the polypeptide shown as SEQ ID NO: 1-10 has response on IgM of a blood sample of a subject integrally or not is taken an index for determining whether the subject is infected by human enterovirus infection or not, and the human enterovirus infection can be diagnosed by more than 94% of sensitivity and lower than 7% of false positive rate. 本发明提供可用于诊断人肠道病毒感染的试剂盒。本发明的检测试剂盒包括个或多个固体载体、以及独立地连接于所述固体载体上的SEQ ID NO：1～10所示的多肽。当以是否SEQ ID NO：1～10所示的多肽整体上对受试者来源的血液样本中的IgM有响应作为判定受试者是否已被人肠道病毒感染的指标的情况下，可以以94％以上的灵敏度和7％以下的假阳性率诊断人肠道病毒感染。